Hadirnya Manajemen Kearsipan sebagai Penunjang Efesiensi Administrasi di Dunia Pendidikan - Setiawan, Heri; Absar, Ulil; Fahmi, Riza; Husein, Sadam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article discusses the importance of archival management in improving administrative efficiency in the field of education. In the context of rapid digitalization, archive management is not only about storage but also a systematic process that supports decision-making. The aim of this study is to identify the impact of modern archival management on educational administration efficiency and the challenges faced in its implementation. The study uses a triangulation method with three data collection sources: archival system observation, interviews with managers, and archival documentation to analyze archival management in educational institutions. The findings indicate that modern archival systems can save up to 30% of document search time and enhance staff productivity. Furthermore, transparency in archive management contributes to accreditation and quality assurance in education. The use of information technology, including cloud-based management systems and artificial intelligence, has proven to increase data accessibility and security. The study shows that integrating archival systems with digital learning platforms can improve teaching and learning efficiency by up to 40%. However, challenges in implementation include budget limitations and the need for skilled human resources. The study also highlights the importance of collaboration between institutions in developing a shared archival system, which can reduce operational costs and improve document accessibility. Sustainability aspects in digital archival management are also a key focus, with research indicating that digital preservation systems can extend the lifespan of archives for up to 25 years. The conclusion of the study emphasizes that effective and integrated archival management not only supports administrative efficiency but also contributes to the overall quality of education. This article calls for investment in the development of archival systems and training for administrative staff to optimize the benefits of this digital transformation.